2010
DOI: 10.1177/0013164410378090
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence of the Wong and Law Emotional Intelligence Scale Across Self and Other Ratings

Abstract: There exist a variety of measurement instruments for assessing emotional intelligence (EI). One approach is the use of other reports wherein knowledgeable informants indicate how well the scale items describe the assessed person's behavior. In other reports, the same EI scales are typically used as in self-reports. However, it is not known whether the measurement structure underlying EI ratings is equivalent across self and other ratings. In this study, the measurement equivalence of an extant EI measure (Wong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
(41 reference statements)
2
26
0
1
Order By: Relevance
“…Hence, these finding can make sense. These outcomes are in agreement with the findings of Karim (2010) and Libbrecht, Lievens and Schollaert (2010). It is partially affirmed by Ngah and Salleh (2015), who confirm the 'use of emotion' as the second highest preferred aspect.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, these finding can make sense. These outcomes are in agreement with the findings of Karim (2010) and Libbrecht, Lievens and Schollaert (2010). It is partially affirmed by Ngah and Salleh (2015), who confirm the 'use of emotion' as the second highest preferred aspect.…”
Section: Discussionsupporting
confidence: 90%
“…These items refer to students' ability to regulate their own emotions (4 items, "I have good control of my emotions" α = .86). The scale was validated with college students in Hong Kong, China (Wong & Law, 2002) and in Europe (Libbrecht, Lievens, & Schollaert, 2010).…”
Section: Methodsmentioning
confidence: 99%
“… Research has confirmed the four‐factor structure of the WLEIS in countries such as the United States (Christie et al., 2007; Joseph & Newman, 2010; Whitman et al., 2009), Turkey (Güleryüz, Güney, Aydin, & Aşan, 2008), Greece (Kafetsios & Zampetakis, 2008), Taiwan (Wang & Huang, 2009), Belgium (Libbrecht, Lievens, & Schollaert, 2010), and Japan (Fukuda, Saklofske, Tamaoka, Fung, Mavaoka, & Kiyama, 2011). The WLEIS has also been used in Canada (Kaushal & Kwantes, 2006), South Korea (Kim, Cable, Kim, & Wang, 2009), Israel (Zysberg & Rubanov, 2010), Barbados (Devonish & Greenidge, 2010), Nigeria (Salami, 2010), and the UK (Lindebaum & Cartwright, 2010).…”
mentioning
confidence: 95%